TANTANGAN PEMBELAJARAN DARING DI INDONESIA - Evi Surahman; Rustan Santaria; Edi Indra Setiawan (Institut Agama Islam Negeri (IAIN) Palopo, 2020)
This article contains the challenges faced by the Indonesian education world in the implementation of online learning. The method used is literature study by collecting various sources that discuss the challenges of online learning in Indonesia. The literature search results show that there are two main challenges to online learning in Indonesia, namely the quality of teachers and infrastructure. Teacher quality is related to the ability of teachers to use information technology in the learning process which is considered to be very low, influenced by age and laptop ownership. Facilities and infrastructure include internet networks that have not yet reached rural areas, unstable internet networks, and costs to buy internet quotas.